2018
DOI: 10.1002/gps.5015
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic factors and the risk of cognitive decline among the elderly population in Japan

Abstract: Aim In Japan, with the largest percentage of population aged 65 years or over, a dementia strategy is needed not only from a medical perspective, but also from a social policy viewpoint. This study aimed to verify the association between socioeconomic factors and cognitive decline among Japanese elderly people. Methods Cognitive decline was assessed over a 15‐year follow‐up period using memory tests or through identifying missing/proxy responses to survey questions due to cognitive dysfunction. I analysed 1886… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Higher prevalence of dementia was found among the younger elderly, aged 65-69 years, in Latin American countries compared with developed nations, whereas the older elderly presented a higher rate of dementia in developed countries (3) . These findings corroborate those of studies associating differences in functional or cognitive performance with social, ethnic, economic, cultural or demographic diversity (4,5,6,7) , as well as with genetic factors (8) . Cognitive-behavioral and functional-structural changes may occur as a result of education, a multidimensional variable that encompasses quality of life, socioeconomic level, and activities of daily living (9) .…”
Section: Introductionsupporting
confidence: 88%
“…Higher prevalence of dementia was found among the younger elderly, aged 65-69 years, in Latin American countries compared with developed nations, whereas the older elderly presented a higher rate of dementia in developed countries (3) . These findings corroborate those of studies associating differences in functional or cognitive performance with social, ethnic, economic, cultural or demographic diversity (4,5,6,7) , as well as with genetic factors (8) . Cognitive-behavioral and functional-structural changes may occur as a result of education, a multidimensional variable that encompasses quality of life, socioeconomic level, and activities of daily living (9) .…”
Section: Introductionsupporting
confidence: 88%
“…Previous empirical studies have suggested that health behavior differed with socioeconomic position [12]. Therefore, the relationship between socioeconomic factors and cognitive function in later life may be determined by cognitive reserve, which refers to an array of factors that provide resilience against neuropathological damage [13] and/or the differences in health behaviors [14]. Socioeconomic disadvantage was reported to be associated with a higher dementia risk, but the mechanism through which socioeconomic factors affect dementia risk is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In this aspect, findings from the Korean urban rural elderly cohort study, in which 3517 participants aged 65 years and older completed baseline assessments, show that Korean older adults residing in a rural area had lower educational attainment, lower household income, and higher rates of heavy drinking, smoking, and being underweight compared with their counterparts residing in an urban area [ 35 ]. By contrast, higher educational attainment, higher household income, and living in advantaged environments were protective of age-related cognitive decline in older adults [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%